A Comparative Study of Permission for Polygamy in Islamic Marriage Law: The Cases of Indonesia and Brunei Darussalam - Mustafid, Mustafid; Akbarizan, Akbarizan; Abdul Munir, Akmal; Faiz Algifari, Muhammad (Syarah: Jurnal Hukum Islam dan Ekonomi, 2025)
Polygamy is a sensitive issue in Islamic marriage law, which is regulated differently in each Muslim country. Indonesia and Brunei Darussalam both adhere to Islamic law, but have different legal approaches to granting permission for polygamy. This study will explore the legal provisions regarding permission for polygamy in Islamic marriage regulations, and will also discuss the similarities and differences in the procedures for granting permission for polygamy between Indonesia and Brunei Darussalam. This study is a comparative normative legal study utilizing the statute approach and comparative approach. The results of the study indicate that Indonesia and Brunei Darussalam both require permission for polygamy based on the principles of fairness and the husband's financial capability, but differ in their procedures and penalties. In Indonesia, permission must be obtained through the Religious Court with the consent of the first wife, while in Brunei, permission is granted by a judge with a penalty of a $2,000 fine for those who marry without written permission. This difference reflects Indonesia's more flexible legal system compared to Brunei, which enforces Islamic law more strictly.